The Combined Role of Nutritional and Inflammatory Status on Mortality in Patients underwent Pericardiocentesis: HALP Score - Tugba Aktemur; Erhan Melikoğlu; Sezgin Atmaca; Mehmet Altunova (OSMANGAZİ JOURNAL OF MEDICINE, 2026)
The main therapeutical option of cardiac tamponade based on percutaneous pericardiocentesis. The predictors of mortality following pericardiocentesis vary. Inflammatory process is the main background of pericardial effusion(PE). Ongoing inflammation may affect short term and long term mortality in patients with PE. HALP score (haemoglobin, albumin lymphocyte and platelet ) involves inflammatory markers and nutritional status and found to be beneficial to predict mortality in various patients. This study aimed to evaluate the prognostic significance of the HALP score for long-term clinical outcomes in patients undergoing pericardiocentesis for cardiac tamponade. The study involved the patients who underwent urgent pericardiocentesis due to cardiac tamponade and the patients who underwent pericadiocentesis due to chronic PE. Primary endpoint is long term mortality. The patients were divided into two groups: survivors group and mortality group. Each group was compared in terms of clinical features, laboratory values and procedural aspects. Results: 227 patients were enrolled into this study. Age, gender, chronic obstructive pulmonary disease, LVEF, malignancy, haemodynamic instability, serum lactate levels and HALP score have been represented as predictors of mortality. After adjusting confounding factors; LVEF [HR: 0.965, 95% CI: 0.939-0.991, p: 0.01],haemodynamic instability[HR: 2.212, 95% CI: 1.279-3.827, p<0.001], malignancy[HR: 3.374, 95% CI: 1.898-5.999, p: 0.005] and HALP [HR: 0.129, 95% CI: 0.019-0.902, p: 0.039] score have been found as independent risk factors of mortality in multivariate regression analysis. The HALP score reflects the combined nutritional and inflammatory status, and a lower HALP score was independently associated with an increased risk of long-term mortality.